Optimization of total flavonoid content of ethanolic extract of Persicaria pulchra (Bl.) Soják for the inhibition of α-glucosidase enzyme - N. H.N. Do; T. M. Le; C. D.P. Nguyen; A. C. Ha (Тонкие химические технологии)
Objectives. There has been a rapid increase in the number of diabetic patients since the past few decades in developed and developing countries. This rapid increase is accompanied by alarming costs of treatment. α-Glucosidase inhibitors are one of the most effective drugs employed for the reduction of postprandial hyperglycemia to manage Type 2 diabetes mellitus. Additionally, flavonoids, a group of natural substances, which are widely distributed in plants and possess variable phenolic structures, exhibit outstanding hypoglycemic activity and are considered as potential α-glucosidase inhibitors. In Vietnam, Persicaria pulchra (Bl.) Soják (P. pulchra) is employed in traditional medications. It possesses high flavonoid contents and its anti-diabetes ability has been hypothesized, although it has attracted less attention for investigation. Hence, the aim of this study is to optimize the condition of the P. pulchra extract to obtain the highest total flavonoid content and measure the bioactivities of P. pulchra, such as the anti-α-glucosidase and antioxidant activities.Methods. The effects of the extracting conditions, including the temperature, extraction time, liquid-to-solid ratio (LSR), and ethanol (C2H5OH) concentration, on the total flavonoid content are investigated via experiments and analyzed by the response surface methodology (RSM). Concurrently, the optimal extraction also determines the anti-α-glucosidase and antioxidant activities.Results. The optimal extraction condition for the highest flavonoid content (530 mg quercetin/g) is determined in 60 min, at 53°C, with LSR of 9.46 g/g and C2H5OH concentration of 62%. Moreover, the optimal plant extract exhibits good α-glucosidase inhibition with a half-maximal inhibitory concentration (IC50) of 22.67 mg/mL, compared to the positive control (acarbose −7.77 g/mL). Additionally, P. pulchra is proposed to be a potential antioxidant with an IC50 of ~12.68 µg/mL.Conclusions. The study confirmed the optimal extraction condition of P. pulchra that will obtain the highest total flavonoid content and revealed the potentials of P. pulchra in α-glucosidase inhibition and antioxidation.